El proceso de enseñanza-aprendizaje de la Lengua y Literatura en el nivel elemental de la unidad educativa “Juan Abel Echeverría. - Millán Ramos, Narcisa Elizabeth (2022)
In the present study entitled: The teaching-learning process of the language and literature at the elementary level of the "Juan Abel Echeverría" educational unit, raised as a research problem the incidence of ignorance of teaching strategies language and literature learning at the elementary level, The objective of this research was to determine the incidence of ignorance of teaching strategies language and literature learning at the elementary level in it, a descriptive methodology was used with a qualitative-quantitative, because his analysis focuses on the educational social problem that seeks to determine the degree of incidence of the teaching-learning process of the language and literature in elementary school students. The population was made up of 90 students from the elementary level made up of the second grade "A", third degree "A", fourth degree "A" to whom a chip of observation; 6 teachers of the level to whom a survey was applied. The results found in the investigation revealed that 67% of teachers do not know playful strategies for teaching and learning of Language and Literature. The students showed difficulty in macro skills; Well, only 31% listen adequately, 12 speak clearly, 21% like to read and barely 18% write comprehensible writing. For this reason, a proposal was made elaboration of a didactic guide of playful teaching learning strategies for the development of macro skills of communication applicable to the level elementary, activities that once applied achieved in the students a better stimulation of the four macro skills (listening, speaking, reading and writing), in addition increased interest and motivation to learn language and literature